A Survey on Energy Efficient Hierarchical Clustering Algorithm for Wireless Sensor Networks (International Journal of Engineering and Computer Science, 2017)
Wireless sensor network are spatially shared out self-directed sensors to observe physical or environmental situations, such as sound, temperature, pressure, and so on as well as to cooperatively go by their data via network to the central location. The extra new networks are bi-directional, too enabling management of the sensor activity. A topology of WSNs could vary from an easy star network to a superior wireless multi-hop mesh network. In this paper we have explained a comprehensive analysis of the current researches on the wireless sensor network. Authors classify the difficulties into three diverse categories. The first is the internal platform as well as underlying operating system. The second is the communication protocol stack. The third is the network services, deployment and provisioning. The node expires in a network if it does not have enough energy. The detailed analysis of routing protocols has defined based upon energy efficiency. Key Words: WSNS, energy efficiency, sensors.